First detection of Nosema ceranae in honey bees (Apis mellifera L.) of the Macaronesian archipelago of Madeira. Issue 3 (27th May 2023) - Lopes, Ana R.; Martín-Hernández, Raquel; Higes, Mariano; Segura, Sara Kafafi; Henriques, Dora; Pinto, M. Alice
Abstract: The Microsporidia Nosema ceranae is an invasive pathogen affecting honey bee health, particularly in warm climates. In this study, N. ceranae was detected for the first time in honey bees ( Apis mellifera L.) of the Madeira archipelago, indicating that this pathogen is now spreading across the entire Macaronesia. Nosema apis was not detected, and the high prevalence (67.7%) of N. ceranae indicates its dominance over N. apis .